Enhanced cytotoxicity of a redox-sensitive hyaluronic acid-based nanomedicine toward different oncocytes via various internalization mechanisms - Yunai Du; Sheng Wang; Tianhao Zhang; Dongsheng He; Jiasheng Tu; Yan Shen (Taylor & Francis Group, 2020)
Receptor-mediated active targeting and tumor microenvironment responsive systems from polymeric micelles have been studied for rapid cellular internalization and triggered drug release. Previously we have constructed redox-responsive polymeric micelles composed of vitamin E succinate conjugated hyaluronic acid (HA-ss-TOS), which are able to actively target CD44 proteins and quickly release loaded drugs upon exposure to high levels of glutathione (GSH) in tumor cells. In the present study, we found that despite different cellular internalization mechanisms, micelles showed strong antineoplastic effects on 4T1 and B16F10 cells due to redox responsiveness. HA-ss-TOS-PTX micelles exhibited an excellent tumor targeting ability and prolonged retention time compared to Taxol in vivo. In addition, a superior antitumor effect was achieved compared to PTX-loaded insensitive micelles (HA-TOS-PTX) and Taxol. Our results revealed that PTX-loaded HA-ss-TOS micelles could enhance the antineoplastic efficacy of PTX for breast cancer and melanoma treatment and, thus, deserve further attention.